FIGURATIVE LANGUAGE IN REY’S BORN TO DIE AND ITS REFLECTION OF STERNBERG’S TRIANGULAR THEORY OF LOVE - Saputri, Ana Andriyani; Nurhamidah, Idha; Wulandari, Diyah Fitri (Universitas Muhammadiyah Lampung, 2025)
This study examines the lyrics of Lana Del Rey's album